The Effect of Work Placement, Work Experience, and Work Environment On Employee Loyalty at The Gorontalo Search and Help Office - Rahmisyari, Rahmisyari (Green Publisher Indonesia, 2022)
Human resource management is very important for government organizations in managing, regulating, and utilizing employees so that they can function productively, realizing an effective, quality and efficient work unit that is able to provide optimal services to the community requires the participation of all elements contained in the work unit. the. This study aims to determine the effect of work placement, work experience, and work environment on employee loyalty at the Gorontalo search and rescue office. The research method used is the Quantitative Research Method, according to Sugiyono (2010:65) Quantitative Research Methods can be interpreted as research based on the philosophy of positivism, used to examine certain populations or samples, research methods in the form of numbers and analysis using statistics. The results show that employee loyalty will increase if the Gorontalo Search and Rescue Office places employees according to their duties and functions. The results of this study indicate that employees in the Gorontalo Search and Rescue Office have been placed in appropriate positions. Although the initial findings of the researcher indicate that there are employees who are placed not according to the educational background completed, but from the results of this study it turns out that education is not the main benchmark for employees to be placed in a field, but employees are placed based on their knowledge, skills and abilities.